2021
DOI: 10.25159/2520-5293/8927
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-containing Hand Rubs: A Survey on Beliefs and Self-reported Practices of Muslim Nurses

Abstract: Although alcohol-containing liquid cleansers have been increasingly used by healthcare workers, their application is still suboptimal. This study was carried out to assess the beliefs and practices of Muslim nurses with respect to alcohol-based hand rub solutions (ABHRs). A total of 374 hospital nurses from a large tertiary referral medical centre in Southern Iran were recruited. Beliefs and self-reported practices toward ABHRs were measured using a structured questionnaire. The validity and reliability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…Thus, this positive attitude towards the standard precautions may reduce the risk of transmission of microorganisms to the patients. Our study corroborates a study conducted by Shiraly et al (6) in 2021. This study also evaluated the students nurse's attitude towards standard precaution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, this positive attitude towards the standard precautions may reduce the risk of transmission of microorganisms to the patients. Our study corroborates a study conducted by Shiraly et al (6) in 2021. This study also evaluated the students nurse's attitude towards standard precaution.…”
Section: Discussionsupporting
confidence: 93%
“…However, previous studies have revealed that the level of knowledge on standard precautions among nursing students appeared to be inadequate (5). Other studies have also shown that nursing students' failure to follow infection control precautions has an impact on not only patients but also other nursing students (6). The previous study by Hambridge et al, (7) in 2021 discovered that accidental wounds from needle stick injuries are common among nursing students and cause a greater psychological impact on an individual.…”
Section: Introductionmentioning
confidence: 99%